Side effects of pesticides used in integrated production of apple in adults of Trichogramma pretiosum - Manzoni, Cristiane Gindri; Grützmacher, Anderson Dionei; Giolo, Fabrizio Pinheiro; Härter, Wagner da Roza; Müller, Cristiane (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the side effects of 12 pesticides used in the integrated production of apple, in laboratory (25±1°C temperature, 70±10% relative humidity and 14 hours photophase), exposing adults of Trichogramma pretiosum to fresh dry pesticide film, in the maximum dosage recommended for field use, with subsequent assessement of the number of eggs parasitized per female. The reduction in the parasitism, compared with the control (water), was used to classify the pesticides as harmless (<30%), slightly harmful (30-79%), moderately harmful (80-99%) and harmful (>99%). The acaricides Envidor (spirodiclofen), Kendo 50 SC (fenpyroximate) and Ortus 50 SC (fenpyroximate), the fungicides Antracol 700 PM (propineb), Midas BR (famoxadone + mancozeb), Palisade (fluquinconazole), Persist SC (mancozeb) and Systhane PM (myclobutanil) and the insecticide Mimic 240 SC (tebufenozide) were harmless; the herbicide Polaris (glyphosate) was slightly harmful; the herbicides Finale (gluphosinate-ammonium) and Roundup Original (glyphosate) were moderately harmful to T. pretiosum.